Characterization of an E1A-CBP Interaction Defines a Novel Transcriptional Adapter Motif (TRAM) in CBP/p300 - O’Connor, Mark J. (American Society for Microbiology, 1999)
The adenovirus E1A protein subverts cellular processes to induce mitotic activity in quiescent cells. Important targets of E1A include members of the transcriptional adapter family containing CBP/p300. Competition for CBP/p300 binding by various cellular transcription factors has been suggested as a means of integrating different signalling pathways and may also represent a potential mechanism by which E1A manipulates cell fate. Here we describe the characterization of the interaction between E1A and the C/H3 region of CBP. We define a novel conserved 12-residue transcriptional adapter motif (TRAM) within CBP/p300 that represents the binding site for both E1A and numerous cellular transcription factors. We also identify a sequence (FPESLIL) within adenovirus E1A that is required to bind the CBP TRAM. Furthermore, an E1A peptide containing the FPESLIL sequence is capable of preventing the interaction between CBP and TRAM-binding transcription factors, such as p53, E2F, and TFIIB, thus providing a molecular model for E1A action. As an in vivo demonstration of this model, we used a small region of CBP containing a functional TRAM that can bind to the p53 protein. The CBP TRAM binds p53 sequences targeted by the cellular regulator MDM2, and we demonstrate that an MDM2-p53 interaction can be disrupted by the CBP TRAM, leading to stabilization of cellular p53 levels and the activation of p53-dependent transcription. Transcriptional activation of p53 by the CBP TRAM is abolished by wild-type E1A but not by a CBP-binding-deficient E1A mutant.